Care of the self : ancient problematizations of life and contemporary thought - Suvák, Vladislav, 1964- (Value inquiry book series, 0929-8436 ; Central European value studies, 2018)
The studies included in the Care of the Self: Ancient Problematizations of Life and Contemporary Thought focus on different manifestations of "taking care of the self" present in ancient and contemporary thought. Each of these studies approaches the issue of taking care of the self from a different perspective: Part I by Vladislav Suvák focuses on Socrates' therapeutic education; Part II by Lívia Flachbartová centres on Diogenes' ascetic practices; and Part III by Pavol Sucharek concentrates on Henri Maldiney's existential phenomenology. Taking care of the self ( epimeleia heautou ) is not just one of a great many topics associated with ancient ethics. Echoing Michel Foucault, we could say that the care of the self applies to all problematizations of life.